(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
In the today’s business environment, experts must do everything to prevent network breaches. Sometimes it is very difficult to identify the attacks coming from nearly all the sides that every vector and point of entry is protected. Attack is a action that exploits vulnerability in controlled system. Recently, there has been an increase in active and passive attacks. An applications that allow for remote access to computers which is known as backdoors that are often used for targeted attacks.And to avoid these types of attack here is a new technique used in Intrusion Detection System that is JAXB technology is used to create the hashmap of complex data.